2021
DOI: 10.2147/rmhp.s288171
|View full text |Cite
|
Sign up to set email alerts
|

Leading Employees Through the Crises: Key Competences of Crises Management in Healthcare Facilities in Coronavirus Pandemic

Abstract: Purpose The fast and shocking onset of the crisis caused by the COVID-19 virus created the need for a complete crisis management of healthcare facilities to manage the current stage of the crisis. The purpose of our research is to examine the relations between the competences of crisis management in healthcare facilities and the performance of employees, measured during the acute stage of the crisis by their feeling of satisfaction, safety and creation of conditions for work, whereby we assume tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Other research conducted in June–September 2020 (two to five months following data collection for the present study) similarly suggested many emergency frontline healthcare workers felt workplace/organisation communication lacked clarity and oftentimes was not timely 36 . Interestingly, reliable and fast sharing of information have been outlined as two crucial components of crisis management for healthcare teams during the COVID‐19 pandemic 59 . While reliability of information may be more difficult to address, given that (particularly during the early stages of a pandemic) information is likely to rapidly evolve as public health authorities learn more about the virus (certainly the case of the early months of COVID‐19), pathways through which information is shared could potentially be streamlined.…”
Section: Discussionmentioning
confidence: 62%
“…Other research conducted in June–September 2020 (two to five months following data collection for the present study) similarly suggested many emergency frontline healthcare workers felt workplace/organisation communication lacked clarity and oftentimes was not timely 36 . Interestingly, reliable and fast sharing of information have been outlined as two crucial components of crisis management for healthcare teams during the COVID‐19 pandemic 59 . While reliability of information may be more difficult to address, given that (particularly during the early stages of a pandemic) information is likely to rapidly evolve as public health authorities learn more about the virus (certainly the case of the early months of COVID‐19), pathways through which information is shared could potentially be streamlined.…”
Section: Discussionmentioning
confidence: 62%
“…Also, Shih et al 38 and Hadley et al 39 found that leaders who lead a crisis effectively have effective communication skills, self-confidence in their capability and enthusiasm to lead in crisis. In addition, Jankelová et al 40 revealed that adequate reaction, effective communication and decision making, self-efficacy and adaptive performance of crisis leaders are key elements of successful crisis leadership. On the contrary, Samuel et al 8 reported a high level of crisis leadership.…”
Section: Discussionmentioning
confidence: 99%
“…The extension of baby boomer nurses’ work (i.e., past retirement age) was also advantageous for both younger bedtime nurses with less experience and hospitals to compensate for the shortage of nurses during the pandemic ( Gan, 2020 ). In terms of adopting appropriate strategies, Jankelová et al (2021) recommended that managers need proper crisis management abilities, including effective decision-making and cooperative communication skills that encourage teamwork. In particular, they confirmed the mediating effect of sharing information, teamwork, and cognitive diversity, and asserted that abundant information and directions helped employees feel safer and raised their productivity during the pandemic.…”
Section: Resultsmentioning
confidence: 99%